Energy Policy of the European Union - Current Situation and Outlook - Pospíšilová, Zuzana; Bič, Josef; Horák, Jiří; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2010)
The first chapter is dealing with the question, what is the contemporary condition of the European governance of the energy sector and what are the causes of the current situation. A comparison with the USA and China can be found here, too. In the second part, there is a decription of the current and future role of the European Union concerning the energy sources, in particular concerning coal, natural gas, oil, nuclear energy, renewables and energy efficiency as well. The last chapter analyses the tendencies of the European Union energy politics and the outlook. The main topics are energy security, the environment and the internal market with electricity and natural gas.
Vedoucí práce: Josef Bič
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2010
Rok obhajoby 2010
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses